2000
DOI: 10.1038/sj.gt.3301175
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cells expressing membrane-bound form of IL-4 induce antitumor immunity

Abstract: Local cytokine concentrations are required for inhibition of tumor growth with less toxic side-effects. However, genetically engineered tumor cells secreting cytokines still induce toxicity and activate bystander cells. To circumvent such problems, membrane-bound forms of IL-4 (IL-4m) were expressed on MethA fibrosarcoma tumor cells. Chimeric forms of IL-4 with the type I transmembrane protein CD4 or type II transmembrane protein TNF were designed to express IL-4 in opposite orientations on the tumor cell surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
1
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 47 publications
0
13
1
1
Order By: Relevance
“…In a previous study, we reported that the tumor cells expressing IL-4 in membrane-bound forms lost tumorigenicity and induced systemic anti-tumor immunity (Kim et al, 2000). These cells were effective in activating CD8 + T cells without noticeable effect on CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we reported that the tumor cells expressing IL-4 in membrane-bound forms lost tumorigenicity and induced systemic anti-tumor immunity (Kim et al, 2000). These cells were effective in activating CD8 + T cells without noticeable effect on CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…We found previously that membrane-bound forms of IL-2 and IL-4 were less stimulatory for T cells when they were expressed as chimeras with CD4, a type I transmembrane protein. 34,38 Alternatively, it is possible that when membrane-bound form might provide an opportunity for it to escape from the protein trafficking restriction operating on the p35 subunit. Cytokine transfer into tumor cells in membrane-bound form has advantages over the secretory form of cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…27 In general, these membrane-anchored cytokines, including IL-2, IL-4, IL-12, IL-21, granulocyte-macrophage colony-stimulating factor, and tumor necrosis factor-α, retain their biological activity and effectively stimulate immune cells and elicit protective antitumor immunity. [28][29][30][31][32][33] As regards IL-12, the in vivo growth rate of tumors transduced with GPI-anchored IL-12 was significantly delayed and the selected tumor clones expressing GPI-IL-12 were completely eliminated. 30 The antitumor effect of GPI-anchored IL-12 can be further enhanced by coexpression of GPI-anchored IL-2 on the same tumor cells.…”
Section: Introductionmentioning
confidence: 99%